2017
DOI: 10.3847/1538-4357/aa63e4
|View full text |Cite
|
Sign up to set email alerts
|

The Solar Energetic Particle Event of 2010 August 14: Connectivity with the Solar Source Inferred from Multiple Spacecraft Observations and Modeling

Abstract: We analyze one of the first solar energetic particle (SEP) events of solar cycle 24 observed at widely separated spacecraft in order to assess the reliability of models currently used to determine the connectivity between the sources of SEPs at the Sun and spacecraft in the inner heliosphere. This SEP event was observed on 2010 August 14 by near-Earth spacecraft, STEREO-A (∼80°west of Earth) and STEREO-B (∼72°east of Earth). In contrast to near-Earth spacecraft, the footpoints of the nominal magnetic field lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 113 publications
(147 reference statements)
1
48
0
Order By: Relevance
“…However, the energetic particle enhancements can be longitudinally even wider than the shock. This may at least partially be attributed to cross-field diffusion in the interplanetary space but also the shock may have been longitudinally wide near the Sun than in the interplanetary space (e.g., Cliver et al 1995;Rouillard et al 2012;Lario et al 2017, and references therein).…”
Section: Particle Acceleration At Icme Shocksmentioning
confidence: 99%
“…However, the energetic particle enhancements can be longitudinally even wider than the shock. This may at least partially be attributed to cross-field diffusion in the interplanetary space but also the shock may have been longitudinally wide near the Sun than in the interplanetary space (e.g., Cliver et al 1995;Rouillard et al 2012;Lario et al 2017, and references therein).…”
Section: Particle Acceleration At Icme Shocksmentioning
confidence: 99%
“…An intercalibration factor of 1/1.4 (1/1.5) has been applied to the ACE (Wind) data to correct the different instrument responses after we compare the ACE/EPAM and Wind/EPACT data with the STEREO measurements. However, since no systematic shifts were found between the estimates from the Parker spiral field line and potential field source surface and other models (Lario et al, 2017), the correlation coefficient and the linear fit relation between CA and theta would not be significantly affected, as shown in Figure 3. To further investigate the Gaussian width of the CA distribution of the SEP peak intensities, we applied a symmetric Gaussian fit centered on 0 = 0 to the 3-SC events, that is, the Gaussian peak is setup at zero CA.…”
Section: Longitudinal Dependence Of Sep Intensitymentioning
confidence: 85%
“…The electron and proton peak intensities used in the Gaussian fit are background-corrected peak values within 48 hr from onset times of the associated Type III radio burst, and the associated local IP shock peaks have been excluded. Lario et al (2017) showed that discrepancy between the estimates from the Parker spiral field line and the potential field source surface model and other magnetohydodynamic models can be as large as ±20 • . An intercalibration factor of 1/1.4 (1/1.5) has been applied to the ACE (Wind) data to correct the different instrument responses after we compare the ACE/EPAM and Wind/EPACT data with the STEREO measurements.…”
Section: Longitudinal Dependence Of Sep Intensitymentioning
confidence: 99%
See 2 more Smart Citations